Manajemen Risiko Keuangan: Penelitian - Takdirmin; Hikmah Idris; Fifi Arfiani; Aqilah Salsabila (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Financial risk management is a systematic process of identifying, measuring, analyzing, and controlling risks related to the financial aspects of a company or organization, with the aim of minimizing potential losses and maximizing profit opportunities. One of the main strategies in mitigating financial risk is diversifying sources of income. Dependence on a single source of funding, such as government funds, can become a serious concern when there are changes in policies or unstable economic conditions. To reduce this dependence, educational institutions can establish partnerships with private entities or set up school business units. The types of financial risk management are credit risk, market risk, operational risk, liquidity risk, legal risk, and equity risk. Educational institutions must be able to manage their budgets well to avoid wastage or imbalance in fund allocation. Educational institutions must be able to manage their budgets well to avoid wastage or imbalance in fund allocation. The rapid growth of risk management services indicates that management can increase company value by controlling financial risks. Therefore, financial managers are able to actively identify and manage the market risks they face.